Seismic structure of rifting in the Okinawa Trough, an active backarc basin of the Ryukyu (Nansei-Shoto) island arc–trench system - Azusa Nishizawa; Kentaro Kaneda; Mitsuhiro Oikawa; Daishi Horiuchi; Yukari Fujioka; Chiaki Okada (Earth, Planets and Space, 2019)
Abstract The Okinawa Trough, to the southwest of Kyusyu, Japan, is an active backarc basin of the Ryukyu (Nansei-Shoto) island arc–trench system caused by the Philippine Sea plate subduction. Unlike other backarc basins around Japan, the Okinawa Trough, ~ 1000 km in length, is unique because the crustal thinning due to backarc rifting is currently in progress in the entire trough. We conducted extensive seismic reflection and refraction surveys to detect detailed variation in seismic structures associated with the rifting tectonics. Seventeen seismic lines were shot, including ten across-trough and seven along-trough lines in the Okinawa Trough. Moho depths estimated mainly from PmP travel times indicate that the crust beneath the trough is thinner than that below the East China Sea shelf and the Ryukyu Island Arc. The shallowest Moho of the across-trough lines was not necessarily detected at the center of the trough, defined as the deepest water depth, but was located beneath the western margin of the northern and middle Okinawa Trough. An M7.1 earthquake occurred in the area on November 14, 2015, and intense aftershock activity was observed along the western margin of the trough. These earthquakes with extension axes of northwest–southeast direction demonstrated that the area is undergoing tectonic rifting. The Moho depth is over 25 km in the northern region of the Okinawa Trough and decreases down to ~ 13 km as it goes to the south, and the thinnest crust of ~ 7 km occurs beneath the Yaeyama Rift in the southern Okinawa Trough. Despite the crustal thinning by the backarc rifting, the P wave velocity models across the Okinawa Trough show that the continental/island arc crust composed of an upper, middle, and lower crusts is continuous between the East China Sea shelf and the Ryukyu Arc. The multichannel seismic profiles along and across the rifts in the southern Okinawa Trough show more volcanic intrusions in the southern side than in the north, which may be related to the position of the volcanic front, which is undetermined in this region.